2011
DOI: 10.2147/ccide.s16860
|View full text |Cite
|
Sign up to set email alerts
|

New phosphated poly(methyl methacrylate) polymers for the prevention of denture-induced microbial infection: an in vitro study

Abstract: Purpose: Poly(methyl methacrylate) (PMMA) has been widely used as a denture-base acrylic resin due to its excellent physical and mechanical properties. However, the material is highly prone to microbial fouling that often leads to Candida-associated denture stomatitis. Incorporation of phosphate groups into PMMA could facilitate adsorption of salivary antimicrobials and inhibit microbial adherence on the polymer surface. An in vitro study evaluated PMMA polymers containing varying amounts of phosphate group fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…PMMA with phosphate groups facilitates adsorption of salivary antimicrobials and inhibits microbial adherence on the polymer surface. The presence of 15% phosphate content in PMMA denture base significantly reduced the saliva‐mediated adhesion of C. albicans and enhanced adsorption of histatin 5 in a phosphate density‐dependent manner . A lower contact angle and a trend toward increased hydrophilicity were observed with an increased concentration of phosphate .…”
Section: Polymeric Biocidesmentioning
confidence: 95%
“…PMMA with phosphate groups facilitates adsorption of salivary antimicrobials and inhibits microbial adherence on the polymer surface. The presence of 15% phosphate content in PMMA denture base significantly reduced the saliva‐mediated adhesion of C. albicans and enhanced adsorption of histatin 5 in a phosphate density‐dependent manner . A lower contact angle and a trend toward increased hydrophilicity were observed with an increased concentration of phosphate .…”
Section: Polymeric Biocidesmentioning
confidence: 95%
“…From the included researches in the systematic review, the modification of MMA was done basically by certain monomers or solutions that can be categorized as fluoromonomers[2627282930] ( n = 5), phosphate monomers[313233] ( n = 3), methacrylic acid monomer[343536373839] ( n = 6), itaconate monomers[404142] ( n = 3), nitromonomers[543444546] ( n = 5), and nonspecific monomers or solutions ( n = 6). Nonspecific monomers include Norbonyl/phenyl methacrylate (NBMA/PHMA),[47] polyhedral oligosilsesquioxane (POSS),[48] methacrylated dendrimer (DD1),[49] 1,3-bis(3-methacryloxypropyl)-1,1,3,3 tetramethyl disiloxane (BMPMS),[50] silver nitrate (AgNO 3 ) solution,[51] and N -acetyl cysteine (NAC).…”
Section: Resultsmentioning
confidence: 99%
“…The monomers used to substitute with MMA (wt/vol%) were either experimentally synthesized[33424445474951] or purchased. [526272829303234353637383940414346485052] For the specimen preparation, the polymer beads were synthesized by bulk polymerization,[29474950] suspension polymerization,[2627283334] or from the commercially available pre-polymers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also reported that when a phosphate-containing monomer was synthesized and combined into PMMA, a significant decline in C. albicans colonization occurred because of the enhanced adsorption of histatin 5 (a type of antimicrobial peptide in saliva) in a phosphate density-dependent manner. 15,16 In addition, self-bonding polymer coatings 12 and hydrophilic coatings 17 have been used to reduce C. albicans adhesion to an antifungal denture.…”
Section: Introductionmentioning
confidence: 99%